2018
DOI: 10.1111/evo.13601
|View full text |Cite
|
Sign up to set email alerts
|

The genetics of phenotypic plasticity. XVI. Interactions among traits and the flow of information

Abstract: Although the environment varies, adaptive trait plasticity is uncommon, which can be due to either costs or limitations. Currently there is little evidence for costs of plasticity; limitations are a more promising explanation, including information reliability. A possible cause for a decrease in information reliability is the channeling of environmental information through one trait that then affects the phenotype of a second trait, the information path. Using an individual-based simulation model, I explored t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…Both recent and earlier studies have shown that the high phenotypic plasticity of plants should not be universally seen as a positive attribute [43,45,110,111]. The plasticity cost might not be pronounced under normal conditions, but when plants are exposed to a highly stressful environment, the plasticity cost might outweigh the fitness gain [112,113]. The results of several studies suggest reduced performance with increasing phenotypic plasticity under stress [38,44].…”
Section: Phenotypic Plasticitymentioning
confidence: 99%
“…Both recent and earlier studies have shown that the high phenotypic plasticity of plants should not be universally seen as a positive attribute [43,45,110,111]. The plasticity cost might not be pronounced under normal conditions, but when plants are exposed to a highly stressful environment, the plasticity cost might outweigh the fitness gain [112,113]. The results of several studies suggest reduced performance with increasing phenotypic plasticity under stress [38,44].…”
Section: Phenotypic Plasticitymentioning
confidence: 99%
“…One way forward includes more developmentally realistic models of plasticity that incorporate multiple traits that interact throughout development (e.g. [237,238]). Building models forces precise articulation of hypotheses and assumptions and generates testable predictions, leading to empirical data, which can feed back to challenge and further develop the theory.…”
Section: (D) Building Underlying Theory Of Integrated Plastic Responses To Suites Of Cues Of Developmental Supportmentioning
confidence: 99%
“…Heritable variation for both ADH activity and ADH plasticity were high, with narrow‐sense heritabilities h2=0.557 and h2=0.776, respectively. From these results, Wang and Althoff () concluded that ADH plasticity is an adaptive trait, which is an important finding because adaptive trait plasticity is uncommon (Scheiner ).…”
mentioning
confidence: 95%